Ethnomathematics in Traditional Culinary Practice: Mathematical Concepts in the Preparation and Sale of Nasi Pecel Tumpang in Kediri, Indonesia - Fatmawati, Eka Nurviana; Mariana, Neni; Ekawati , Rooselyna (Papanda Publisher, 2025)
This study explores the presence of mathematical concepts embedded within the traditional culinary process of Nasi Pecel Tumpang, a renowned dish from Kediri, Indonesia. Utilizing an autoethnographic approach combined with semi-structured interviews, the researcher investigates personal childhood experiences and supports them with interviews conducted with local food vendors to uncover mathematical practices inherent in the preparation, processing, and sale of this cultural delicacy. The study involved five traditional food vendors selected through purposive sampling. The findings reveal that daily culinary activities — often seen as routine or informal — contain rich mathematical values, including counting, measurement, comparison, fractions, ratios, sequencing, geometry, and data representation. During the preparation stage, vendors engage in mathematical thinking through the use of standard units (grams, liters), whole number operations (addition, subtraction), and estimation (e.g., handfuls, pinches). The cooking process involves the use of ordinal numbers to sequence tasks, time measurement for boiling or frying ingredients, and length measurement when cutting vegetables. Moreover, elements of geometry are evident in the shapes of utensils and food arrangement, while proportional reasoning is applied in the formulation of spice blends. In the post-production stage, mathematical applications expand to pricing strategies, revenue calculation, and data tabulation using basic statistical tools such as means, frequency tables, and pictograms. The study underscores the value of integrating local cultural practices into mathematics education, offering a contextualized learning experience that is both meaningful and culturally relevant to students. Specific research questions guided the inquiry, focusing on how traditional culinary activities reflect mathematical thinking and how these insights can inform classroom practices. By leveraging familiar cultural artifacts like traditional foods, educators can foster greater student engagement, reduce math anxiety, and build stronger connections between academic content and everyday life. This research contributes to the broader field of ethnomathematics and highlights the importance of culturally responsive pedagogy in elementary education, particularly in areas rich with cultural heritage.